Penentuan Titik Rawan Kecelakaan Pada Ruas Jalan Mahar Martanegara Kota Cimahi - Yusmiati Kusuma; Risna Rismiana Sari; Lilla anjani Birahmatika; Linda Aisyah; Ardianto Tri Pradityo; Kevin Hutama Syahputra (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2026)
Mahar Martanegara Road in Cimahi City serves as a strategic urban corridor connecting Cimahi and Bandung, characterized by high traffic volume influenced by surrounding industrial, residential, and commercial land use. The volume-to-capacity ratio approaching saturation conditions has increased traffic conflicts and accident risks in recent years. This study identify and analyze accident prone locations (blackspots) along Mahar Martanegara Road using the Equivalent Accident Number (AEK), Upper Control Limit (UCL), and Upper Control Boundary (BKA) methods. Accident data from 2022–2024 obtained from PT Jasa Raharja were analyzed and segmented per 300 meters. The AEK was calculated using weighted severity values for fatalities and injuries, and the results were statistically evaluated using BKA and UCL thresholds. The analysis indicates that two road segments categorized as blackspots is STA 0+600–0+900 and STA 2+400–2+700. The AEK values for these segments are 27 and 33, respectively, exceeding the BKA value (25.69) and their corresponding UCL values STA 0+600–0+900 (23.99) and STA 2+400–2+700 (24.94). These findings suggest systematic accident patterns beyond normal statistical variation. Contributing factors include high traffic density, the presence of heavy vehicles, roadside activities, inadequate safety facilities, and geometric and operational constraints. The results provide a data driven basis for local government intervention through traffic engineering improvements, enhancement of road safety facilities, regulation of heavy vehicle movement, and integrated road safety management strategies.